Compatibility of pesticides and the management of major insect-pests of rice - Sarao, P S; Sandhu, R K; Rani, B Jhansi (Indian Journal of Plant Protection, 2021)
Two insecticides viz., Spinetoram 6% + methoxyfenozide 30% and Triflumezopyrim (10.6%), and two fungicides viz., Hexaconazole (5%) and Tricyclazole (75%) were evaluated singly and in combination against major rice insect-pests at the Rice Research Area, Punjab Agricultural University, Ludhiana during Kharif 2017 and 2018. Among the different combinations tested, Spinetoram 6% + methoxyfenozide 30% was found to be superior for the control of stem borer and leaf folder damage whereas, Triflumezopyrim (10.6%) was effective against planthoppers. However, the combination of Spinetoram 6% + methoxyfenozide 30% + Hexaconazole (5%) treatment recorded highest yield as compared to other treatments. No reduction in their efficacy was recorded when used as a tank mix application in the field.